1998
DOI: 10.1093/clinchem/44.6.1184
|View full text |Cite
|
Sign up to set email alerts
|

Detection and identification of monoclonal gammopathies by capillary electrophoresis

Abstract: Capillary electrophoresis (CE) and immunosubtraction capillary electrophoresis (IS-CE) were compared with the conventional methods agarose gel electrophoresis (AGE) and immunofixation electrophoresis (IFE) for detection and identification of paraproteins. In total, 74 paraproteins out of 468 serum samples were detected by both methods. Seventy-three monoclonal bands with concentrations ranging from 0.6 to 50.9 g/L were detected by the routine method. With CE, 70 paraproteins were detected and quantified on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 12 publications
1
15
1
Order By: Relevance
“…Moreover, better resolution of different fractions is obtained by CZE compared with other techniques, especially when large and poorly defined spikes are present. 6 The higher resolution of CZE compared with CAE is emphasized in the 2 cases in this report in which 2 distinct paraproteins with similar migration patterns were produced, giving rise to a single large spike by CAE analysis. Rarely, paraproteins are not detected by CZE or AGE.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…Moreover, better resolution of different fractions is obtained by CZE compared with other techniques, especially when large and poorly defined spikes are present. 6 The higher resolution of CZE compared with CAE is emphasized in the 2 cases in this report in which 2 distinct paraproteins with similar migration patterns were produced, giving rise to a single large spike by CAE analysis. Rarely, paraproteins are not detected by CZE or AGE.…”
Section: Discussionmentioning
confidence: 70%
“…In a human study, both techniques showed higher sensitivity in detecting monoclonal spikes compared with standard CAE (98%, 93%, and 83% for CZE, AGE, and CAE, respectively) with similar specificity (91%, 91%, and 94%, respectively). Moreover, better resolution of different fractions is obtained by CZE compared with other techniques, especially when large and poorly defined spikes are present 6 . The higher resolution of CZE compared with CAE is emphasized in the 2 cases in this report in which 2 distinct paraproteins with similar migration patterns were produced, giving rise to a single large spike by CAE analysis.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations